1985
DOI: 10.1177/0310057x8501300404
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Function in Platelet Concentrates and in Whole Blood

Abstract: Platelet function was studied in CPD whole blood stored at 4QC for one and three days and in platelet concentrates stored at room temperature for the same periods of time. Comparisons were made of platelet shape, nucleotide content, (3-thromboglobulin ((3TO) liberated during storage, and platelet aggregation in response to ADP, collagen, sodium arachidonate and ristocetin. It was found that in whole blood the shape of the platelets was less discoid than in platelet concentrates. However, platelet aggregation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Further, PLT counts decreased significantly during storage in the studies of Jobes et al [21] and Pidcoke et al [22] without any correction of the results for this confounder. Further, Kornblith et al [24] compared fresh WB to expired PLT concentrates and Rodgers et al [23] only examined up till 3 days of storage, thereby making direct comparisons with the current study difficult.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…Further, PLT counts decreased significantly during storage in the studies of Jobes et al [21] and Pidcoke et al [22] without any correction of the results for this confounder. Further, Kornblith et al [24] compared fresh WB to expired PLT concentrates and Rodgers et al [23] only examined up till 3 days of storage, thereby making direct comparisons with the current study difficult.…”
Section: Discussionmentioning
confidence: 85%
“…Nonetheless, the PLT aggregation capacity of WB is at least as good as it is in BCP or AP. Previous studies have shown reduced PLT aggregation capacity in BCP and AP during storage as measured by light transmission aggregometry [12][13][14][15][16][17][18] or multiple electrode aggregometry [12,13,19,20], but only few have compared PLT function in BCP or AP to that of WB [23,24]. Knowledge of PLT function in WB during storage is sparse and has shown conflicting results [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…let-activating factor (PAF). I 5 * l 6 For instance, PAF causes a rapid turnover of phosphoinositides in platelets, which then leads to platelet aggregation and serotonin secretion. I7-I9 In the present investigation, we monitored the phosphoinositide turnover in PRP because we thought it relevant to study platelet responses in a milieu closer to that in which platelets exist in vivo.…”
mentioning
confidence: 99%